2023
DOI: 10.5603/fm.a2022.0073
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature study of trachea and bronchus morphology in children and adults

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This is particularly challenging during the intraoperative period owing to the lack of routine radiographic confirmation. Variations in the tracheal length have been reported in multiple studies with different racial populations 1 , including Indian 2 4 , Asian 5 – 8 , and Caucasian 9 . The length of vocal cord-to-carina (VC-Carina) in males were larger than females, and also correlated with height 5 – 7 ; however, the current practice of ETT selection takes only sex and airway diameter into account.…”
Section: Introductionmentioning
confidence: 96%
“…This is particularly challenging during the intraoperative period owing to the lack of routine radiographic confirmation. Variations in the tracheal length have been reported in multiple studies with different racial populations 1 , including Indian 2 4 , Asian 5 – 8 , and Caucasian 9 . The length of vocal cord-to-carina (VC-Carina) in males were larger than females, and also correlated with height 5 – 7 ; however, the current practice of ETT selection takes only sex and airway diameter into account.…”
Section: Introductionmentioning
confidence: 96%
“…However, our study did not independently measure RA and LA, which may limit a comprehensive analysis of sex differences. Additionally, we considered the factor of weight, which was not accounted for in previous research [ 19 ], and found a positive correlation between SCA and weight ( Figure 7C ). Despite this correlation, multivariate linear regression analysis indicated that weight does not significantly predict changes in SCA ( Table 1 ).…”
Section: Discussionmentioning
confidence: 95%
“…Comparative studies in mammals have demonstrated that the sternocleidomastoid muscle frequently separated into five parts which are arranged in two layers: a superficial sternomastoid, sternooccipital and cleidooccipital part; and a deep layer consisting of a deep sternomastoid and cleidomastoid part. In humans, the presence of multiple layers such as sternocleidooccipital, cleidomastoid and sterno- [5] mastoid, a supernumerary cleido-occipital muscle, more or less separate from the sternocleidomastoid [6] muscle have been reported. In many animals, the cleidomastoid belly is distinctly separate from the sternomastoid belly.…”
Section: Discussionmentioning
confidence: 99%